The Effect of Third-Party Funds on Net Profit at PT Bank Mega Syariah with Financing as Intervening Variable - Rizky Ananda Utami; Nurbaiti Nurbaiti; Wahyu Syarvina (LPPM UIKA Bogor, 2022)
The purpose of this study was to determine the effect of TPF (Third Party Funds) on Net Profit at PT Bank Mega Syariah, to determine the effect of Financing on Net Profit at PT Bank Mega Syariah, and to determine the effect of TPF (Third Party Funds) through Financing on Profit. Net at PT Bank Mega Syariah. This type of research is field research using quantitative methods. Data collection techniques using documentation in the form of financial statements of PT Bank Mega Syariah. The data analysis technique used path analysis using the SPSS 22 application. The results showed that TPF (third party funds) had a positive and significant effect on net income at PT Bank Mega Syariah of (0.962) with a significant value (0.000). Financing has a negative and insignificant effect on net income at PT Bank Mega Syariah by (-0.622) with a significant value (0.561). TPF (Third Party Funds) through financing has a negative and insignificant effect on net income at PT Bank Mega Syariah by (- 0.268) with a significant value (0.694).